Contribuição da estruturação da Atenção Primária à Saúde segundo seus atributos essenciais para a qualidade da Assistência em Saúde Mental: um estudo a partir do PMAQ-AB - Antonio Moacir de Jesus Lima (2021)
The insertion of mental health in primary care is underway in the country. In order to know this reality, we opted for the mixed study with two distinct sequential phases in which the first Quantitative provides the data for the second qualitative phase. The quantitative study aimed to verify whether the primary care teams in Brazil that have the attributes of Primary Health Care (PHC) better structured are able to offer good care in Mental Health. For this, it has two very distinct phases. Cross-sectional study based on data from the 2nd cycle of the Program for Improving Access and Quality in Primary Care, referring to the 29,778 Primary Care Teams that were evaluated by the program. Data were collected in the external evaluation phase from 2013 to 2014. Two types were created: Quality of mental health care (dependent variable) and structuring of PHC according to its essential attributes (independent variable). For the typology of structuring PHC according to the attributes, the Delphi technique was used to reach consensus regarding the questions that would be used to compose each attribute. The variables used were endorsed by four specialists. For the typology of quality of care in Mental Health, questions related to this content were identified. Sums of the questions were performed to categorize the indexes. Then, through multinomial logistic regression analyzes, the association between the two typologies was sought and later, it was identified which attribute most contributed to the quality of mental health care. Almost a third (29.2%) of the teams are in a poor level of structuring the quality of assistance in Mental Health, with the majority of the teams being at the medium level. Only (18.7%) of the teams are at the high level. For the structuring of PHC there is a small number of teams (7.5%) at the low level of structuring, (5.93%) at the high level and the majority (86.52%) is also at the medium level. Regional differences are maintained both for structuring PHC and for the quality of mental health care, with the best rates in the South and Southeast regions and the worst in the North and Central-West regions. The contribution of attributes to the structuring of the quality of mental health care is different in the best and the worst scenario. Comprehensiveness is the attribute that contributes the most in the best scenario and the Coordination attribute in the worst scenario. The associations were positive for all attributes. The result for the broad-PHC attribute (sum of the essential attributes) showed a 14.7 times greater chance of producing a better quality of mental health care when PHC is structured. Having a high level of comprehensiveness is also associated with having a high level of quality of mental health care (OR: 3.21). It is concluded that there is a predominance of low levels of quality of care in the area of mental health, highlighting the need for integrated and coordinated actions for this area in PHC in Brazil. Qualitative study - second phase: the second phase was developed through a qualitative study, guided by ethnomethodology and the results found in phase I (quantitative) guided the discussions of phase II (qualitative) in order to deepen the discussions on the theme. The findings of the first phase confirmed the initial hypothesis of the study that the teams participating in the PMAQ-AB that have the essential attributes of PHC better structured are more likely to offer a better quality of assistance in the area of mental health. Thus, the objectives of the second phase were to understand: 1) How PHC teams with the best PHC structuring provide assistance in the mental health area and 2) How the PHC teams with the worst PHC structuring provide assistance in the mental health area. To this end, individual and collective interviews were conducted with managers, coordinators and professionals from PHC teams. The research was carried out in five municipalities in the Vale do Jequitinhonha region, Minas Gerais State, in the nine-month period (April to December) of 2019. The teams that accepted the invitation to participate in the study were included in the study, whose managers signed the Informed Consent Form (ICF) and who had both high and low quality in the provision of health care as well as structuring PHC in its different attributes. As an instrument for data collection, five individual interviews were conducted with municipal managers and six interviews with PHC coordinators. The collective interviews totaled ten and were in the form of Discussion Groups. All material collected was recorded, transcribed in full and analyzed in depth. Some of the main thematic categories that emerged were: unveil the world of intramural mental disorders through home visits and presence at school; distinct universes with traditional formats to mental health problems arising from social networks; expansion of approach and support for mental health patients and perception by PHC teams of the transfer of stigmas that operate in the mental health network. This study complies with the regulatory norms and guidelines for research involving human beings of Resolution 466/2012, with approval by the Institutional Review Board of Universidade Federal de Minas Gerais, under Registration 28804, approved on 05/30/2012.